Current Topics in Lactation - Gigli, Isabel (IntechOpen, 2017)
Lactation is a fascinating process. Research over the last decade has provided new insights into the regulation of mammary gland development and involution. Lactation is the last step in reproduction, and therefore it is linked to reproduction strategy. Photoperiod species such as sheep, or pseudo-ovulatory (at mid-gestation) species as the rodent Lagostomus maximus, are interesting and unique models to study mammary gland physiology. This book also offers updated insights into the mechanisms that control postlactational involution, therefore also providing information to better understand breast cancer. Small noncoding RNA has opened new understanding in gene regulation. In this regard, our knowledge of mammary gland development and milk secretion has increased extremely. This book provides current scientific information on all these interesting topics. It will certainly be of great benefit to those interested in biomedical sciences.